Marcella an "idillio moderno" in three episodes - Pizzech, Alessio; Ricchetti, Matteo; Daolio, Serena; Formaggia, Danilo; Dilengite, Pierluigi; Natalizia, Carone; Girardi, Angelica; Procházka, Pavel 1949-; Benzi, Manlio (Naxos, 2009)
This centenary performance of Umberto Giordano's Marcella was prepared from the composer's manuscript, the score and parts having been destroyed during World War II. Recalling Verdi's La Traviata and Puccini's La Rondine, as well as Giordano's own Andrea Chenier and Fedora, Marcella is the story of a poor girl and a painter whose illicit affair is shattered when events reveal that her true love is actually a prince incognito.
Interpr. u.a.: Serena Daolio (Marcella). Danilo Formaggia (Giorgio). Pierluigi Dilengite (Drasco). Natalizia Carone (Clara). Angelica Girardi (Raimonda). Orchestra Internazionale d'Italia. Slovak Chamber Choir. Pavol Procházka (Choreinstud.). Manlio Benzi (Dir.). Alessio Pizzech (Bühnenregie). Matteo Ricchetti (Filmregie). - Aufn.: Martina Franca, Palazzo Ducale, 33. Festival of the Valle d'Itria, 4. - 6. August 2007
Keywords: Operas; DVD-Video